Endohedral Lithium-containing Fullerenes : Preparation, Derivatization, and Application - Matsuo, Yutaka; Okada, Hiroshi; Ueno, Hiroshi (Springer Singapore : Imprint: Springer, 2017)
This book describes the emergent endohedral metallofullerene, lithium-containing fullerene Li@C60, with an overview from its history to recent application research. The book covers synthesis, preparation, purification, structure, physical and chemical properties, derivatization, computational theoretical studies, and device application of Li@C60. Readers can learn cutting-edge nanotechnology of this exotic nanocarbon material, which is expected to deliver future solutions in clean energy and bio devices. This work is by a researcher who has long experience in carbon nanomaterials-more than 15 years with his contributing coworkers. The level of the book is appropriate for graduate students, post-docs researchers, and young faculty members who are interested in nanomaterials from the point of view of chemistry and physics.
Keywords: Chemistry.; Organic chemistry.; Nanochemistry.; Nanoscale science.; Nanoscience.; Nanostructures.; Nanotechnology.; elektronické knihy; electronic books